Phylogenomic disentangling of the Bifidobacterium longum subsp. infantis taxon. Issue 7 (28th July 2021) - Tarracchini, Chiara; Milani, Christian; Lugli, Gabriele Andrea; Mancabelli, Leonardo; Fontana, Federico; Alessandri, Giulia; Longhi, Giulia; Anzalone, Rosaria; Viappiani, Alice; Turroni, Francesca; van Sinderen, Douwe; Ventura, Marco
Abstract : Members of the Bifidobacterium longum species have been shown to possess adaptive abilities to allow colonization of different mammalian hosts, including humans, primates and domesticated mammalian species, such as dogs, horses, cattle and pigs. To date, three subspecies have formally been recognized to belong to this bifidobacterial taxon, i.e. B. longum subsp. longum, B. longum subsp. infantis and B. longum subsp. suis . Although B. longum subsp. longum is widely distributed in the human gut irrespective of host age, B. longum subsp. infantis appears to play a significant role as a prominent member of the gut microbiota of breast-fed infants. Nevertheless, despite the considerable scientific relevance of these taxa and the vast body of genomic data now available, an accurate dissection of the genetic features that comprehensively characterize the B. longum species and its subspecies is still missing. In the current study, we employed 261 publicly available B. longum genome sequences, combined with those of 11 new isolates, to investigate genomic diversity of this taxon through comparative genomic and phylogenomic approaches. These analyses allowed us to highlight a remarkable intra-species genetic and physiological diversity. Notably, characterization of the genome content of members of B. longum subsp. infantis subspecies suggested that this taxon may have acquired genetic features for increased competitiveness in the gut environment of suckling hosts. Furthermore, specific B. longum subsp. infantis genomic features appear to be responsible for enhanced horizontal gene transfer (HGT) occurrences, underpinning an intriguing dedication toward acquisition of foreign DNA by HGT events.